2019
DOI: 10.3892/ijmm.2019.4276
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 enhances mechanical stress-induced cardiomyocyte hypertrophy in�vitro via the RAGE/ERK1/2 signaling pathway

Abstract: Pressure overload-induced cardiac hypertrophy is associated with a complex spectrum of pathophysiological mechanisms, including the inflammation response. High mobility group box-1 (HMGB1), a pro-inflammatory cytokine, is not only increased in myocardium under pressure overload, but also exacerbates pressure overload-induced cardiac hypertrophy and dysfunction; however, the underlying mechanisms have remained elusive. In the present study, cultured cardiomyocytes were stimulated by mechanical stress and/or HMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…RAGE is well known to play an important role in adipocyte hypertrophy and mediating various inflammatory signals [28]. In concordance with the increased expression of RAGE and RAGE ligands in the fat tissue of obese animals, the ratio of RAGE and RAGE ligand binding also increased.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…RAGE is well known to play an important role in adipocyte hypertrophy and mediating various inflammatory signals [28]. In concordance with the increased expression of RAGE and RAGE ligands in the fat tissue of obese animals, the ratio of RAGE and RAGE ligand binding also increased.…”
Section: Resultsmentioning
confidence: 83%
“…In high-fat diet conditions, RAGE ligands are secreted more when compared to lean conditions and bind to RAGE [27]. Adipocyte hypertrophy is known to be induced by a signaling pathway between RAGE and its ligands [28,29]. Downstream signals of RAGE upregulate the transcription of nuclear factor kappa-light-chain-enhancer β (NF-κB) and thus mediate the secretion of inflammatory cytokines [30].…”
Section: Resultsmentioning
confidence: 99%
“…Several differentially expressed genes identified in this study, including HMGB1, ROCK2, and Jak2, are amenable in principle to diagnostic biomarkers and therapeutic targets. Previous studies indicated that upregulation of HMGB1 aggravated mechanical stress-induced cardiomyocyte hypertrophy via the RAGE/ERK1/2 signaling pathway [ 23 ]. Increased ROCK2 was associated with the pathogenesis of Ang-II-induced cardiac hypertrophy via regulating FHOD3 phosphorylation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, administration of a specific TLR4 blocker, viral inhibitory peptide within the paraventricular nucleus, downregulated HMGB1 in both circulation and brain, and this was accompanied by downregulation of pro-inflammatory cytokines as well as improvement of cardiac hypertrophy (48). Another study investigated HMGB1 in H9c2 cells, and found that HMGB1 alone had no influence in cardiac hypertrophy but aggravated myocardial hypertrophy in the context of pressure/mechanical stress stimulation, which also caused a prompt upregulation of the expression of TLR4 in cardiomyocytes (61). Consequently, the TLR4/HMGB1 axis may be a new therapeutic target for cardiac hypertrophy.…”
Section: High Mobility Group Boxmentioning
confidence: 99%
“…In addition, inhibition of extracellular HSP70 (one of the TLR4 ligands) binding to TLR4 was found to attenuate pressure overloadinduced cardiac hypertrophy and fibrosis by modulating ERK and p38 MAPK activity (46), further corroborating the previous studies. It is interesting to note that blocking TLR4 appeared to exert no effect on activation of ERK1/2 following stimulation of extracellular HMGB1 (one of the TLR4 ligand) in mechanical stress-induced cardiomyocyte hypertrophy in vitro (61), suggesting that various ligands may activate TLR4 downstream different pathways. Furthermore, a new regulatory mechanism for TLR4/MAPK signaling has been identified.…”
Section: Tlr4/myd88/mapk Pathwaymentioning
confidence: 99%